The sparid fishes of Pakistan, with new distribution records - Siddiqui, Pirzada Jamal; Amir, Shabir Ali; Masroor, Rafaqat (Zootaxa, 2014)
The family sparidae is represented in Pakistan by 14 species belonging to eight genera: the genus Acanthopagrus with four species, A. berda, A. arabicus, A. sheim, and A. catenula; Rhabdosargus, Sparidentex and Diplodus are each represented by two species, R. sarba and R. haffara, Sparidentex hasta and S. jamalensis, and Diplodus capensis and D. omanensis, and the remaining four genera are represented by single species, Crenidens indicus, Argyrops spinifer, Pagellus affinis, and Cheimerius nufar. Five species, Acanthopagrus arabicus, A. sheim, A. catenula, Diplodus capensis and Rhabdosargus haffara are reported for the first time from Pakistani coastal waters. The Arabian Yellowfin Seabream Acanthopagrus arabicus and Spotted Yellowfin Seabream Acanthopagrus sheim have only recently been described from Pakistani waters, while Diplodus omanensis and Pagellus affinis are newly identified from Pakistan. Acanthopagrus catenula has long been incorrectly identified as A. bifasciatus, a species which has not been recorded from Pakistan. All species are briefly described and a key is provided for them.